Holistic Islamic Education: An Implementation Study of Knowledge Integration within the Muhammadiyah Curriculum - Baidarus, Baidarus; Fithri, Radhiyatul; Aisyah, Riha Datul (Journal of English Language and Education, 2025)
Islamic education in the modern era is increasingly challenged to remain relevant amidst rapid technological advancement, globalization, and the dominance of secular knowledge. In response, there is a growing need to integrate general scientific knowledge with Islamic values to create a holistic educational framework. This article explores the development strategy of Islamic education programs that combine scientific approaches with religious and moral principles to construct a comprehensive, value-based learning system. Using a qualitative descriptive method, this study employs literature review and document analysis to explore various models and practices of integrative education. The documents analyzed include the official Muhammadiyah curriculum, teaching guidelines from the Muhammadiyah Council for Primary and Secondary Education, and academic literature related to the integration of science and Islamic values. The findings reveal that the integration of science and Islamic values not only enriches the learning experience but also significantly contributes to the formation of students’ character, ethical awareness, and critical thinking. It fosters a balanced mindset that harmonizes spiritual, intellectual, and social dimensions. Consequently, integrative Islamic education programs are essential for preparing a generation that is not only intellectually competent but also morally grounded, culturally aware, and ready to address the multidimensional challenges of the global era.